2022
DOI: 10.1037/emo0000924
|View full text |Cite
|
Sign up to set email alerts
|

Infant fecal microbiota composition and attention to emotional faces.

Abstract: The gut microbiota has been suggested to influence neurodevelopment in rodents.Preliminary human studies have associated fecal microbiota composition with features of emotional and cognitive development as well as differences in thalamus-amygdala connectivity. Currently, microbiota-gut-brain axis studies cover heterogenous set of infant and child brain developmental phenotypes, while microbiota associations with more finegrained aspects of brain development remain largely unknown. Here (N=122, 53% boys), we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…Similarly, in early neural development, the developing microbiome appears to be particularly sensitive during early life and its profile can be altered by external stimuli, including stress, adversity, diet, environmental microbes, and antibiotics, with both immediate and long-term negative effects on the integrity of the immune system, metabolism, and overall health [17][18][19]. Such perturbations during sensitive periods of development have also been linked to negative cognitive outcomes [20][21][22], socioemotional function-ing [23][24][25][26], and internalizing and externalizing problem behaviors [21,22], all of which have serious implications for various neurodevelopmental disorders.…”
Section: Gut Microbiota and Clinical Symptomatology In Asdmentioning
confidence: 99%
“…Similarly, in early neural development, the developing microbiome appears to be particularly sensitive during early life and its profile can be altered by external stimuli, including stress, adversity, diet, environmental microbes, and antibiotics, with both immediate and long-term negative effects on the integrity of the immune system, metabolism, and overall health [17][18][19]. Such perturbations during sensitive periods of development have also been linked to negative cognitive outcomes [20][21][22], socioemotional function-ing [23][24][25][26], and internalizing and externalizing problem behaviors [21,22], all of which have serious implications for various neurodevelopmental disorders.…”
Section: Gut Microbiota and Clinical Symptomatology In Asdmentioning
confidence: 99%
“…Studies have also reported that some bacterial genes and specific bacteria can also be applied for the diagnosis of cardiovascular diseases, , and there may even be some potential therapeutic values for the occurrence and development of diseases. , However, there are many factors influencing intestinal microbes. In addition to the diseases and other factors, there are reports that different exercise methods, psychological factors, and bad living habits can also affect intestinal microorganisms. , …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the diseases and other factors, there are reports that different exercise methods, psychological factors, and bad living habits can also affect intestinal microorganisms. 10,11 Smoking is universal among populations in various countries, and its harm is great, resulting in the occurrence and development of many diseases. Besides, smoking, a risk factor, is easily overlooked in scientific research, so it is a major interference factor in scientific analysis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, in new-borns (25 days old), Bifidobacterium enrichment is associated with negative emotionality (Bifidobacterium pseudocatenulatum) and emotion regulation/orienting (Bifidobacterium pseudocatenulatum and Bifidobacterium catenulatum). However, in infants, an abundance of Bifidobacterium (along with lower Clostridium) at 2.5 months has been associated with reduced "fear bias" (i.e., attention toward fearful versus happy/neutral faces) at 8 months [28]. Similarly, in a Chinese cohort (12 months olds), Bifidobacterium was related with Soothability [29], whereas Hungatella (also associated with constipation and eczema in children [30]) was associated with reduced Cuddliness.…”
Section: Microbiome and Early Life Temperamentmentioning
confidence: 94%